Fractal characteristics and theirs influence on methane adsorption in high-rank coals with NMR - Jiang, Wei; Zhou, Ying; Wu, Caifang; Du, Mingyang (Frontiers in Earth Science, 2023)
To further understand the pore structure characteristics and their effect on CH4 adsorption capacity for high-rank coals. Based on 11 fresh coal samples from the Zhina coalfield of South China. We analyzed the pore structure characteristics of coal samples by low-temperature liquid-nitrogen adsorption (LP-N2A) measurements. On the basis of nuclear magnetic resonance (NMR), we obtained the fractal dimensions of different types of pores by the new model, studied the relationship between the fractal dimensions, and the characteristic parameters of coals (composition and pore characteristics) and discussed the influence of the fractal dimensions on CH4 adsorption. The results show that according to LP-N2A isotherms, all coals can be classified into three types. The micropores provide the largest proportion of the specific surface area (SSA) of coals. Two fractal dimensions, Da (adsorption pore) and Ds (seepage pore), ranged from 2.471 to 2.805 and from 2.812 to 2.976, which were acquired in the saturated water condition by NMR. Furthermore, Da and Ds have different correlations with ash yield, carbon contents, moisture, SSA and irreducible fluid porosity. The coal composition and pore parameters have much greater control over fractal dimensions. Moreover, the different fractal dimensions have different influences on methane adsorption. With the increase of Da, the methane adsorption capacity is enhanced, but it is weakened with the increase of Ds. The high-rank coals have more SSA with higher Da and provide more adsorption sites for CH4. Langmuir pressure PL has different correlations with fractal dimensions. Da decreases with the increase of PL. The adsorption velocity is faster with higher Da. Thus, the fractal dimensions are the comprehensive reflection of differences among the physical properties of coal and are able to show the effect of coal properties on methane adsorption fully.